Enhancing CASEL 5 Social and Emotional Competencies in Engineering Students through Flipped and Gamified Blended Learning: A Longitudinal Study - Sarppa Raje, M.; Arjunan, M. (Journal of Engineering Education Transformations, 2026)
Engineering education increasingly requires integration of social-emotional learning (SEL) alongside technical competencies. Flipped and gamified blended learning approaches show promise for holistic skill development, yet empirical evidence remains limited. This longitudinal study examines the impact of a flipped and gamified blended learning model on the development of CASEL 5 Social and Emotional Learning (SEL) competencies among undergraduate Computer Science and Engineering students over four years (2019-2023). A total of 960 undergraduate computer science students were assigned to experimental (n=480; flipped-gamified instruction) or control conditions (n=480; traditional didactic instruction). Two specialized instructors delivered pedagogy-specific interventions. CASEL 5 competencies were assessed via validated self-report instruments and classroom observations at three time points (pre-, mid-, post-intervention). Academic performance and engagement were measured through exam scores and behavioral ratings. Repeated measures ANOVA revealed statistically significant improvements in all CASEL 5 domains for the experimental group compared to controls (all p<0.001, effect sizes Cohen's d ranging from 0.68 to 0.89). Self-management showed the largest improvement with Cohen's d equal to 0.89. Academic performance significantly improved in the experimental group with Cohen's d equal to 1.52. Classroom engagement ratings increased by 34% in the experimental group versus 12% in the control group. Flipped-gamified blended learning effectively enhances social-emotional competencies and academic outcomes in engineering students. Findings support scalable pedagogical models integrating SEL within technical curricula, though triangulation with objective behavioral measures is needed to confirm self-reported gains.